Validation of Abbreviated Form of the Multidimensional Prognostic Index (MPI): The BRIEF-MPI Project - Cella A; Veronese N; Custodero C; Castagna A; Cammalleri LA; Capitano WM; Solimando L; Carruba L; Sabbà C; Ruotolo G; Barbagallo M; Pilotto A (Clinical Interventions in Aging, 2022)
Alberto Cella,1 Nicola Veronese,2 Carlo Custodero,3 Alberto Castagna,4 Lisa A Cammalleri,1 Walter M Capitano,2 Luisa Solimando,2 Luca Carruba,2 Carlo Sabbà,3 Giovanni Ruotolo,4 Mario Barbagallo,2 Alberto Pilotto1,3 1Department of Geriatric Care, Orthogeriatrics and Rehabilitation, E.O. Ospedali Galliera, Genova, Italy; 2Geriatric Unit, Department of Internal Medicine and Geriatrics, University of Palermo, Palermo, Italy; 3Department of Interdisciplinary Medicine, University of Bari “Aldo Moro”, Bari, Italy; 4Geriatrics Unit, “Pugliese Ciaccio” Hospital, Catanzaro, ItalyCorrespondence: Alberto Pilotto, Via delle Mura Capuccine, 14, Genova, 16128, Italy, Tel +39 010 5634400, Fax +39 010 5634400, Email alberto.pilotto@galliera.itPurpose: To screen multidimensional frailty in older people, using a comprehensive geriatric assessment (CGA) tool such as the multidimensional prognostic index (MPI), is a public health priority. Unfortunately, the screening tools available are not able to capture multidimensional frailty. In this work, we aimed to evaluate in a population of hospitalized and ambulatory older patients, the agreement between an abbreviated form of the MPI (ie, BRIEF-MPI) and the standard/full version.Participants and Methods: All participants included in the study completed both versions of the MPI, brief and full, which share the following domains: 1) basic and 2) instrumental activities of daily living, 3) mobility/risk of pressure sores, 4) cognition, 5) nutrition, 6) comorbidity, 7) social and 8) number of medications. The agreement between the two instruments was reported using either the mean comparisons with a t-test matched sample, a simple correlation analysis and the Bland–Altman methodology.Results: The study sample included 110 participants (mean age=83.2 years, 51.8% women). The mean difference was statistically and clinically irrelevant (mean difference=0.01± 0.10; p=0.27). The correlation between brief and full MPI versions was optimal (R=0.82, p< 0.0001). Using the Bland–Altman methodology, we observed that only three participants over 110 (=2.73%) were outside the limits of agreement. The accuracy of BRIEF-MPI in predicting multidimensional frailty, as full MPI> 0.66, was optimal (area under the curve=0.92, p< 0.0001). A BRIEF-MPI value of 0.59 yielded the highest sensitivity and specificity in predicting multidimensional frailty.Conclusion: BRIEF-MPI had a good agreement with the full/standard version of the MPI, making this tool as ideal for the screening of multidimensional frailty in older people.Keywords: multidimensional prognostic index, screening, frailty, agreement